Mechanical Modulation of Colossal Magnetoresistance in Flexible Epitaxial Perovskite Manganite. (16th July 2020) - Yen, Min; Lai, Yu‐Hong; Kuo, Chang‐Yang; Chen, Chien‐Te; Chang, Chun‐Fu; Chu, Ying‐Hao
Abstract: Heteroepitaxially flexible oxide systems have been intensely developed and considered as the most promising materials for leading the creation of next‐generation flexible electronic devices. Among them, perovskite manganites have attracted significant attention with their abundant and novel properties such as colossal magnetoresistance (CMR) and metal‐insulator transition. However, the requirement of high quality samples hampers this field, not to mention the advanced nanoengineering. In this study, fluorophlogopite mica (F‐mica) is selected as a flexible substrate to fabricate heteroepitaxial Pr0.5 Ca0.5 MnO3 (PCMO) with a nanocolumn structure. Through a precise control of thickness, different morphologies are realized to manipulate the magnetotransport properties (reduction of melting field). Moreover, thanks to the excellent flexibility of F‐mica, mechanical modulation of CMR (≈1000%) can be achieved in different flex modes while the magnetic properties remain unaffected. Detailed bending tests are performed to study the behavior of resistive change (≈30%). Through the combination of high flexibility, high quality PCMO, and well‐designed nanocolumn structure, the study exhibits the significant controllability of CMR via mechanical bending, and manifests the potential of such a heteroepitaxially flexible oxide system which can be applied on flexible magnetoresistive devices and sensors. Abstract : A flexible Pr0.5 Ca0.5 MnO3 /F‐mica heteroepitaxy with a nanocolumn structure is developed. Through precise control of thickness and flexion, the mechanical modulation of colossal magnetoresistance can reach near 1000%. Typical bending tests also exhibit a mechanical modulation of resistive tunability of about 30%. This flexible epitaxial perovskite manganite shows the potential on flexible magnetoresistive devices and sensors.